2016
DOI: 10.1007/s00127-016-1323-3
|View full text |Cite
|
Sign up to set email alerts
|

Holocaust exposure and subsequent suicide risk: a population-based study

Abstract: This study partly converges with findings identifying Holocaust survivors (full direct exposure) as a resilient group. A tentative mechanism for higher vulnerability to suicide risk of the partial direct exposure group from countries with higher genocide exposure includes protracted guilt feelings, having directly witnessed atrocities and escaped death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A second concern relates to methodological differences among studies. For example, studies reviewing the mental health impact of genocides have investigated a variety of outcomes, including depression, anxiety, schizophrenia [4, 5], suicide [6, 7], post-traumatic stress as well post-traumatic growth. Some studies documented a negative impact, while others found resilience or no association notwithstanding immense cruelties to which survivors had been exposed.…”
Section: Introductionmentioning
confidence: 99%
“…A second concern relates to methodological differences among studies. For example, studies reviewing the mental health impact of genocides have investigated a variety of outcomes, including depression, anxiety, schizophrenia [4, 5], suicide [6, 7], post-traumatic stress as well post-traumatic growth. Some studies documented a negative impact, while others found resilience or no association notwithstanding immense cruelties to which survivors had been exposed.…”
Section: Introductionmentioning
confidence: 99%